2013
DOI: 10.1089/end.2013.0315
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasonic Propulsion of Kidney Stones: Review and Update of Preclinical Technology

Abstract: Introduction: A noninvasive tool to reposition kidney stones could have significant impact in the management of stone disease. Our research group has developed a noninvasive transcutaneous ultrasound device. A review and update of the current status of this technology is provided. Discussion of Technology: Stone propulsion is achieved through short bursts of focused, ultrasonic pulses. The initial system consisted of an eight-element annular array transducer, computer, and separate ultrasound imager. In the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…The results also broaden the application of ultrasonic propulsion beyond facilitating the passage of small stones to potentially repositioning a large stone from the ureteropelvic junction into the pelvis or a calyx to relieve pain or to reposition a large stone from a calyx to the pelvis before shock wave lithotripsy or ureteroscopy. 4 It was not tested, but there may be sufficient force to dislodge an obstructing stone in the ureter or to detach a stone forming on tissue or Randall plaque. 6 …”
Section: Discussionmentioning
confidence: 99%
“…The results also broaden the application of ultrasonic propulsion beyond facilitating the passage of small stones to potentially repositioning a large stone from the ureteropelvic junction into the pelvis or a calyx to relieve pain or to reposition a large stone from a calyx to the pelvis before shock wave lithotripsy or ureteroscopy. 4 It was not tested, but there may be sufficient force to dislodge an obstructing stone in the ureter or to detach a stone forming on tissue or Randall plaque. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic propulsion was performed with a custom-built clinical prototype, including an ultrasound imaging transducer (ATL/Philips C5-2 probe), Verasonics Ultrasound Engine (Redmond, WA), computer processor, and touchscreen, as previously described. 2,4 The user identifies a stone under B-mode ultrasound. Touching the stone on the monitor triggers delivery of the acoustic push to the targeted location.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Potential applications of this technology in the management of upper tract stones include facilitating passage of small stones or residual stones after lithotripsy, pre-or intraoperative repositioning of renal stones, and moving an obstructing stone to a nonobstructing position. 4 A potential barrier to the adoption of this technology by urologists may be the skill required to operate a diagnostic ultrasound imager and interpret ultrasound images. Experience from animal studies with this technology has shown that effective targeting to push stones requires user skills, including an understanding of the spatial anatomy of the collecting system, visualization of the stone, and alignment of the acoustic force with the desired stone trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…In medical ultrasound, radiation force is a basis for new imaging modalities (Sarvazyan et al, 1998;Tanter et al, 2009). Another recent promising application is the ability to noninvasively expel stones from the kidney (Sorensen et al, 2013).…”
Section: Acoustic Streaming and Radiation Forcementioning
confidence: 99%